A novel polymer-derived method to prepare Eu-doped Si3N4 yellow phosphor. Issue 3 (April 2015) - Li, Quan; Gong, Chaoyang; Cheng, Xuan; Zhang, Ying
Abstract: The yellow emission europium-doped silicon nitride (Si3 N4 :Eu) phosphor was prepared by a new and facile synthesis route via precursor formed by reacting solid polycarbosilane with europium acetylacetonate hydrate followed by nitridation and calcination of the precursor. This novel polymer-derived method utilized both distinctive polymer reaction and organic–inorganic transformation; accordingly, the amount of 4 wt% Eu mainly in the form of Eu 3+ was uniformly doped into Si3 N4 (α and β):Eu nanocrystallites at mild conditions. The double-exponential photoluminescence behavior with the decay time of 1.18 ns and 25.28 ns corresponding to the 4f 6 5d 1 −4f 7 transition of Eu 2+ and 4f–4f transition of Eu 3+, respectively, was observed with Si3 N4 (α and β):Eu when excited at 375 nm and emitted at 550 nm.